Short Movie in EFL Classroom: EFL Learners’ English Speaking Achievement - Iman, Jaya Nur (LPPM Universitas Bina Sarana Informatika, 2025)
Integrating short movies seems to be interesting and exciting in English speaking classroom. This inquiry was aimed at investigating the effect of short movies with retelling technique on English speaking achievement. Six research questions were tailored to predict. A quasi-experimental research design which was merely concerned on comparison group research design was used in this research. Purposive sampling was employed in which it consisted of twenty eight participants with equal size comprising of fourteen participants, respectively. An English speaking assessment as the instrumentation was performed with analytical scoring rubric used to collect the data of EFL learners’ speaking performance. The research process was successfully done to answer predicted six research questions. In conclusion, using short movie with retelling technique gave significant improvement on EFL learners’ English speaking analytically and holistically as the p value was lower than conventional level of significance. Besides, the percentage distribution to respective aspect of speaking was fluency (88.7%), vocabulary (7.5%), pronunciation (2.1%), comprehension (.7%), and grammar (.6%). Some thorough and systematic conclusions and pedagogical implications were tactfully written out. Key words: short movie, EFL classroom, retelling technique, English speaking achievement